1990
DOI: 10.1203/00006450-199009000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Modulation of Neuroendocrine Function: Developmental Changes in Gonadotropin-Releasing Hormone Secretion during Sexual Maturation

Abstract: ABSTRACT. To assess sleep-associated changes in gonadAbbreviations otropin-releasing hormone secretion during sexual maturation, we studied nighttime and daytime patterns of LH and FSH secretion in two groups with qualitatively similar sex steroid levels: girls with central precocious puberty and young adult women in the early follicular phase of an ovulatory menstrual cycle. In the girls with central precocious puberty, all indices of LH secretion were significantly higher at night than during the day (mean L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…However, because of the superimposed effects of sleep on these hormones, it is less clear that the 24-h excursions of gonadotropin and gonadal hormone levels in men and women represent a true circadian rhythm. Nighttime augmentation of gonadotropin levels is a hallmark of puberty (Boyar et al, 1972;Kapen et al, 1974;Landy et al, 1990;Wu et al, 1996). However, sleep-reversal studies have shown that this is due to the stimulatory effect of sleep on LH secretion rather than to a true circadian effect (Kapen et al, 1974).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because of the superimposed effects of sleep on these hormones, it is less clear that the 24-h excursions of gonadotropin and gonadal hormone levels in men and women represent a true circadian rhythm. Nighttime augmentation of gonadotropin levels is a hallmark of puberty (Boyar et al, 1972;Kapen et al, 1974;Landy et al, 1990;Wu et al, 1996). However, sleep-reversal studies have shown that this is due to the stimulatory effect of sleep on LH secretion rather than to a true circadian effect (Kapen et al, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…However, as is the case with a number of other hormonal systems such as growth hormone (GH) and PRL (Czeisler and Klerman, 1999;Van Cauter et al, 2001), sleep has a profound influence on reproductive hormone secretion. There is a sleep-associated increase in pulsatile luteinizing hormone (LH) secretion during puberty in boys and girls (Boyar et al, 1972;Kapen et al, 1974;Landy et al, 1990;Wu et al, 1996) as well as in adult men (Luboshitzky et al, 2001;Schiavi et al, 1992;Veldhuis et al, 2000) and a sleep-associated slowing of pulsatile LH secretion in young women that is most notable in the early follicular phase (Filicori et al, 1986;Hall et al, 1992;Hall et al, 2005;Rossmanith et al, 1993;Soules et al, 1985). Twenty-four-hour diurnal rhythms of follice-stimulating hormone (FSH) (Mortola et al, 1992) and LH have been documented in the setting of normal sleep/ wake routines.…”
mentioning
confidence: 99%